'God Was Here First': Value, Hierarchy, and Conversion in a Melanesian Christianity. Issue 3 (27th May 2019) - Macdonald, Fraser
ABSTRACT: Throughout the world, conversion to evangelical and Pentecostal Christianity produces what Joel Robbins calls 'duplex cultural formations', whereby surviving aspects of local cosmology and worldview are brought into tension with paramount Christian values through a process of critical evaluation. I explore the dynamics of this process within Oksapmin understandings of human and cosmic origins. Traditional anthropogonic models explaining the emergence of lineages from primordial figures have been brought into tension with more-valued understandings of God as creator of the universe through the process of diabolisation, in this case, local figures being associated with fallen angels expelled from Heaven. I argue that these beings are permitted to continue because the anthropogenic and historic nature of their power does not significantly contradict the cosmogonic and eternally present conception of God's creative capacity, but are diabolised owing to their continued existence as symbols of creative power and the source of sinful ritual practices.